A formal construction of certificateless proxy multi-signature scheme. (2016) - Jin, Zhengping; Wang, Qing; Li, Zhongxian
Proxy multi-signature is a scheme that allows a proxy signer to sign messages on behalf of a group of original signers. To our best knowledge, most of the existing proxy multi-signature schemes are proposed in public key infrastructure or identity-based setting. However, owing to avoiding the inherent escrow problem of identity-based cryptography and yet not requiring certificates to guarantee the authenticity of public keys, certificateless public key cryptography has become an attractive paradigm on which many cryptographical primitives are based. In this paper, a generic construction and a formal security model of certificateless proxy multi-signature (CLPMS) is defined. A concrete CLPMS scheme is also proposed, which is proven to be existentially unforgeable against adaptively chosen warrant attacks and chosen message and identity attacks in the random oracle model under the computational Diffie-Hellman assumption.